Corruption, criminalisation of politics and development - Shamshad, Ahmad; Ansari, Nafees Ahmad (2008)
The article analyses the ills of corruption and criminalisation of politics affecting the masses. Corruption and criminalisation of politics have become rampant in Indian society, because of low literacy, little awareness and almost non-existing confidence and courage to challenge authorities. To check the increasing menace of corruption and growing criminalisation of politics, there is an urgent need to create awareness among the masses so that the benefits of the policy of the government could reach the people. Corruption is a collusive act between the bribe giver and bribe taker. But ultimately the victim is the society as a whole. Gunner Myrdal rightly said that, "the prevalence of corruption provides strong inhibitions and obstacles to development". Still, there is hope, all politicians are not criminals and all bureaucrats are not corrupt; some of them are still holding the truth, and it is because of them that the system is still functioning. So. by taking these honest people into confidence, we can march forward and check the evils by all possible means. - Reproduced.
Keywords: Politics and government; Corruption; Political corruption